2013
DOI: 10.1111/vaa.12042
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ammonium sulfate gradient loaded liposome–encapsulated oxymorphone and hydromorphone in healthy dogs

Abstract: Objective To evaluate the pharmacokinetics, in dogs, of liposome-encapsulated oxymorphone and hydromorphone made by the ammonium sulfate gradient loading technique (ASG). Animals Four healthy purpose-bred Beagles aged 9.5 ± 3.2 months and weighing 13.4 ± 2.3 kg. Study Design Randomized cross-over design. Methods Each dog was given either 4.0 mg kg−1 of ASG-oxymorphone or 8.0 mg kg−1 of ASG-hydromorphone SC on separate occasions with a 3-month washout period. Blood was collected at baseline and at serial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…A nonpainful injection site bulge was reported in dogs receiving a long-acting formulation, although histology was not performed (Gutierrez et al, 2014). There were no skin reactions in our previous studies with liposomal Loading Liposome Doxycycline Pharmacokinetics Efficacy 1243 at ASPET Journals on April 30, 2020 dmd.aspetjournals.org morphine, hydromorphone, and oxymorphone tested in rats, dogs, and nonhuman primates Smith et al, 2003Smith et al, , 2013. In the present study, STD-doxy-injected skin samples had a greater probability of having no lesions compared with LE-DPPC doxy-injected samples.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…A nonpainful injection site bulge was reported in dogs receiving a long-acting formulation, although histology was not performed (Gutierrez et al, 2014). There were no skin reactions in our previous studies with liposomal Loading Liposome Doxycycline Pharmacokinetics Efficacy 1243 at ASPET Journals on April 30, 2020 dmd.aspetjournals.org morphine, hydromorphone, and oxymorphone tested in rats, dogs, and nonhuman primates Smith et al, 2003Smith et al, , 2013. In the present study, STD-doxy-injected skin samples had a greater probability of having no lesions compared with LE-DPPC doxy-injected samples.…”
Section: Discussioncontrasting
confidence: 38%
“…Liposomes have long been studied as a drug delivery system (Hunt et al, 1979). Variations in liposome composition, formation, and loading methodology may lead to strikingly different drug concentrations and release kinetics for a particular drug (Hunt et al, 1979;Omri et al, 1995;Omri and Ravaoarinoro, 1996;Sangaré et al, 1998;Krugner-Higby et al, 2003Smith et al, 2003Smith et al, , 2013Budai et al, 2009). Our laboratory has developed a novel liposome loading methodology (Heath et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Grant and coworkers demonstrated that a phospholipid-morphine liposome had prolonged activity and greater safety in mice than the free drug [ 14 ]. Lipid-based carrier strategies have been refined for the delivery of several opiates [ 15 ]. Pontani and Misra described a cholesterol-triglyceride matrix for the long-term delivery of drugs to treat chronic pain and opiate addiction [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grant and coworkers demonstrated that a phospholipid-morphine liposome had prolonged activity and greater safety in mice than the free drug [ 13 ]. Liposomal strategies have been refined for the delivery of several opiates [ 14 ]. Pontani and Misra described a cholesterol-triglyceride matrix for the long-term delivery of drugs to treat chronic pain and opiate addiction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%